2022
DOI: 10.3390/antiox11030567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Pomace Polyphenols and In Vitro Gastrointestinal Digestion on Antimicrobial Activity: Recovery of Bioactive Compounds

Abstract: Grape pomace (GP), a major byproduct obtained from the winemaking process, is characterized by a high amount of phenolic compounds and secondary plant metabolites, with potential beneficial effects on human health. Therefore, GP is a source of bioactive compounds with antioxidant, antimicrobial, and anti-inflammatory activity. As people are paying more attention to sustainability, in this work, we evaluate two different extractions (aqueous and hydroalcoholic) of GP bioactive compounds. In vitro simulated gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 70 publications
2
31
0
1
Order By: Relevance
“…Previous results showed the capacity of bacteria to grow in the presence of polyphenols as they metabolize them. A positive correlation between bacteria effects and the modification of pH during gastrointestinal digestion was observed; in fact, in the presence of digested grape pomace extracts, Gram-positive (Bacillus megaterium and Listeria monocytogenes) and Gram-negative (Escherichia coli) bacteria were inhibited, while a probiotic Lactobacillus plantarum grew, as shown in Caponio et al [ 107 ]. In line with these results, our group is performing a study on the anticancerogenic effects of digested grape pomace extracts in human colon cancer cell lines.…”
Section: Fruit Componentsmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous results showed the capacity of bacteria to grow in the presence of polyphenols as they metabolize them. A positive correlation between bacteria effects and the modification of pH during gastrointestinal digestion was observed; in fact, in the presence of digested grape pomace extracts, Gram-positive (Bacillus megaterium and Listeria monocytogenes) and Gram-negative (Escherichia coli) bacteria were inhibited, while a probiotic Lactobacillus plantarum grew, as shown in Caponio et al [ 107 ]. In line with these results, our group is performing a study on the anticancerogenic effects of digested grape pomace extracts in human colon cancer cell lines.…”
Section: Fruit Componentsmentioning
confidence: 69%
“…Grape pomace is a major by-product obtained from the winemaking process that contain phenolic compounds with beneficial effects on human health. Recently, we evaluated the antioxidant effects of grape pomace digested extracts [ 107 ], evaluating in vitro models their prebiotics and probiotic activities. Previous results showed the capacity of bacteria to grow in the presence of polyphenols as they metabolize them.…”
Section: Fruit Componentsmentioning
confidence: 99%
“…Several studies have demonstrated that the in vitro gastrointestinal digestion increased the bioaccessibility of polyphenols [ 23 , 25 ]. Thus, in this study we determined the antioxidant activity, the total phenolic content (TPC), and the polyphenolic composition of the GP gastrointestinal digested extract.…”
Section: Resultsmentioning
confidence: 99%
“…One of these is represented by the concept of bioavailability of polyphenols, which in turn depends on the relative content of compounds released from the food matrix along the digestive system (bioaccessibility), the digestive stability, and the efficiency of the transepithelial passage (intestinal absorption) [ 20 , 21 , 22 ]. As previously published, the in vitro simulated gastrointestinal digestion of GP extracts improved the bioavailability and bioaccessibility of polyphenols with a consequent increase in both antioxidant activity and phenolic compound content [ 23 ]. A useful option to evaluate the bioactivity effects of these extracts consists in using cell lines that reproduce in vitro the mechanisms of action in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, no health effects were considered, but other in vivo experiments report favorable health effects when administering a grape pomace extract to hypertensive rats, according to its high content of phenolics in general and anthocyanins in particular [ 102 ]. These compounds can also exert antimicrobial effects against some species ( Escherichia coli , Bacillus megaterium, and Listeria monocytogenes ) [ 103 ], potentially exerting other health effects on the consumers, but further experiments are required to demonstrate them conclusively.…”
Section: Selected Foods Enriched With Agro-industrial Fruit Byproduct...mentioning
confidence: 99%